Anthocyanin contents and molecular changes in rose petals during the post-anthesis color transition - Ying Kong; Huan Wang; Li Qiu; Xiaoying Dou; Lixin Lang; Jinrong Bai (Ornamental Plant Research)
Flower color transitions during anthesis are taxonomically widespread; however, the mechanisms underlying post-anthesis color transition in roses are unclear. In this study, we collected petals of the butterfly rose (Rosa chinensis 'Mutabilis'), a post-anthesis color change cultivar, at different developmental stages and under different treatments. Anthocyanin composition and transcriptome data were analyzed to identify the environmental factors and crucial genes involved in post-anthesis color transition. The results showed that sunlight is a key factor triggering color transition. In butterfly rose flowers, color transition results from an increase in the accumulation of anthocyanins, primarily cyanidin-3-O-glucoside, and cyanidin-3,5-O-diglucoside. A combination of genome-wide identification, RNA-seq analysis, bioinformatics analysis, and quantitative real-time PCR verification revealed that RcUF3GT1 and RcGSTF2 genes were involved in anthocyanin production and anthocyanin transport, respectively. RcMYB114a may play a significant role in anthocyanin biosynthesis during color transition in roses, and RcBBX28 might be a crucial gene involved in this process. These insights contribute to our knowledge of flower color change and have implications for further research on plant genetics and flower color evolution.